Higher education in Egypt and needed employability skills in the domestic labor market: case study from Ain Shams University, faculty of engineering - Daoud, Wafaa (AUC Knowledge Fountain, 2012)
The purpose of this empirical study is to find out to what extent employability skills needed by the domestic market are embedded in the Public University curricula, and especially in Ain Shams, faculty of engineering curricula. In the terms of curriculum improvement the study will be conducted to assess two components: the first component is to figure out the employability skills needed for engineering careers in the domestic labor market in Egypt, and the disadvantages related to the non acquisition of these skills in the career of engineering. The second component is to assess the engineering students' self perceived level of competence at performing the basic employability skills, and whether the skills are embedded in the engineering curriculum or not. A total of ten Employers and human resources personnel were interviewed to achieve the first component of the study. The interviewers reported that the changing environment of market requires skills in communication, team work, problem solving, planning and organizing, initiative and enterprise, self management, decision making, and technological adoption. They considered the employability skills the meaningful tool for graduate engineers to achieve and maintain successful participation in the workplace To assess student skill levels, a concessive sample of 140 engineering students from Ain Shams University in Egypt responded to the modified questionnaire "Engineers Generic Employability Skills". The descriptive results indicate that the students have moderate or minor competence in most of the employability skills. Those competences are acquired mostly outside the University. This indicates a need to modify the engineering curriculum to allow for further practice of the employability skills demanded domestically in Egypt.